2014
DOI: 10.4269/ajtmh.13-0444
|View full text |Cite
|
Sign up to set email alerts
|

Autochthonous Blastomycosis of the Adrenal: First Case Report from Asia

Abstract: Abstract. Systemic endemic mycoses, such as blastomycosis, are rare in Asia and have been reported as health risks among travelers who visit or reside in an endemic area. Adrenal involvement is rarely seen in blastomycosis and has never been reported from Asia. We report the first case of blastomycosis with bilateral involvement of the adrenals in a diabetic patient residing in the state of Arunachal Pradesh, India.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 15 publications
0
11
0
Order By: Relevance
“…The soil near lakes, rivers or streams is considered a risk location for infection [1], [4]. Other than the endemic regions, blastomycosis has been reported in Africa, India, Europe, and Central America [1], [2], [3], [4], [7], [8]. There is one case report each from Israel and Saudi Arabia, and there are many human case reports in India, but only five cases have been conclusively proven to be blastomycosis [7], [8].…”
Section: Introductionmentioning
confidence: 99%
“…The soil near lakes, rivers or streams is considered a risk location for infection [1], [4]. Other than the endemic regions, blastomycosis has been reported in Africa, India, Europe, and Central America [1], [2], [3], [4], [7], [8]. There is one case report each from Israel and Saudi Arabia, and there are many human case reports in India, but only five cases have been conclusively proven to be blastomycosis [7], [8].…”
Section: Introductionmentioning
confidence: 99%
“…Siderits et al reported adrenal mass in a case of disseminated Blastomycosis. Kumar et al reported a case of adrenal Blastomycosis from North East India. They diagnosed B. dermatitidis on the basis of morphology which appeared as thick‐walled, broad‐based budding yeast cells on Gomori Methenamine Silver stain and thin septate hyphae bearing spherical to pyriform smooth‐walled microconidia on gram stained smears from Sabouraud dextrose agar culture.…”
Section: Discussionmentioning
confidence: 99%
“…reported adrenal mass in a case of disseminated Blastomycosis. Kumar et al26 reported a case of adrenal Blastomycosis from North East India.They diagnosed B. dermatitidis on the basis of morphology which appeared as thick-walled, broad-based budding yeast cells on Gomori Methenamine Silver stain and thin septate hyphae bearing spherical to pyriform smooth-walled microconidia on gram stained smears from Sabouraud dextrose agar culture. Laboratory tests such as serology, complement fixation, precipitation test, latex particle agglutination test, agar-gel double immunodiffusion test, radioimmunoassay, and polymerase chain reaction may help in diagnosis of histoplasmosis,27 yet the gold standard for a definite diagnosis of histoplasmosis is tissue culture 28.…”
mentioning
confidence: 99%
“…Blastomyces dermatitidis is a dimorphic fungus that is rarely reported from India; no well-defined area of endemicity in that part of the world has been recorded ( 1 ). However, it is endemic to the Ohio and Mississippi River valleys of North America and the states bordering the Great Lakes ( 2 ).…”
mentioning
confidence: 99%
“…Severe pulmonary disease can occur in apparently immunocompetent, as well as immunocompromised, persons ( 3 ). Persons from non–disease-endemic areas usually acquire this disease during travel to disease-endemic areas ( 1 ).…”
mentioning
confidence: 99%